Impact of Xbox Gaming on Object control skills and Balance for children with autism spectrum disorder-A Pilot study (Indian Journal of Physiotherapy and Occupational Therapy - An International Journal, 2024)
Background: Children with ASD could face difficulties in a variety of areas including object handling skills andbalance. These issues can impair their ability to accomplish everyday tasks, participate in physical activity andsuccessfully communicate with their surroundings.Purpose: To determine the impact of xbox gaming on object control skills and balance for children with ASD.Methods: A pilot study was conducted with a total of 20 ASD children who were allocated into two groups.The experimental group (n=10) received xbox gaming and the conventional group received conventional therapy(n=10) The therapy was provided for 40 minutes five days a week for eight weeks to both groups. The test of grossmotor development scale-2 and a pediatric balance scale were used to determine the before and post-test values ofObject control skills (OCSs) & Balance.Results: The results findings shows that the experimental group pre and post-test values using the test of grossmotor development scale-2(14.2±4.04,33±8.02) and conventional group (12.2±4.56,23.2±2.85) have a p valueof
Keywords: Pediatric balance scale,Test of gross motor development scale-2,Xbox gaming,Object control skills